Homodimeric Minimal Factor H: In Vivo Tracking and Extended Dosing Studies in Factor H Deficient Mice - Kamala, Ola; Malik, Talat H.; Hallam, Thomas M.; Cox, Thomas E.; Yang, Yi; Vyas, Falguni; Luli, Saimir; Connelly, Chloe; Gibson, Beth; Smith-Jackson, Kate; Denton, Harriet; Pappworth, Isabel Y.; et al. (Frontiers in Immunology, 2021)
C3 glomerulopathy (C3G) is associated with dysregulation of the alternative pathway (AP) of complement and treatment options remain inadequate. Factor H (FH) is a potent regulator of the AP. An in-depth analysis of FH-related protein dimerised minimal (mini)-FH constructs has recently been published. This analysis showed that addition of a dimerisation module to mini-FH not only increased serum half-life but also improved complement regulatory function, thus providing a potential treatment option for C3G. Herein, we describe the production of a murine version of homodimeric mini-FH (mHDM-FH (mFH1–5^18–20^R1–2)), developed to reduce the risk of anti-drug antibody formation during long-term experiments in murine models of C3G and other complement-driven pathologies. Our analysis of mHDM-FH indicates that it binds with higher affinity and avidity to WT mC3b when compared to mouse (m)FH (mHDM-FH KD=505 nM; mFH KD=1370 nM) analogous to what we observed with the respective human proteins. The improved binding avidity resulted in enhanced complement regulatory function in haemolytic assays. Extended interval dosing studies in CFH-/- mice (5mg/kg every 72hrs) were partially effective and bio-distribution analysis in CFH-/- mice, through in vivo imaging technologies, demonstrates that mHDM-FH is preferentially deposited and remains fixed in the kidneys (and liver) for up to 4 days. Extended dosing using an AAV- human HDM-FH (hHDM-FH) construct achieved complete normalisation of C3 levels in CFH-/- mice for 3 months and was associated with a significant reduction in glomerular C3 staining. Our data demonstrate the ability of gene therapy delivery of mini-FH constructs to enhance complement regulation in vivo and support the application of this approach as a novel treatment strategy in diseases such as C3G.